Synthesis and thermal modification of N-substituted functional polymaleimides - Chung, CM; Ahn, KD (WILEY-V C H VERLAG GMBH, 1997)
Syntheses, advantageous thermal modification and properties of variously N-substituted functional polymaleimides are described. Specific thermal properties of the polymers monitored by thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) are summarized. The facile modification of the functional polymaleimides by thermal or acid-catalyzed deprotection offers versatile means in functional transformation and lithographic application of the polymers.
Keywords: POLYMERIZATION; THERMOLYSIS; POLYMERS